Towards the Hybrid Library: Developments in UK Higher Education - Rusbridge, Chris (IFLA, 2000)
The real world in which information professionals struggle to provide high quality services is not the simple world of most so-called "digital library" services, but rather is characterised by complexity and diversity in almost all aspects of the information access chain. Dealing with diversity is the real problem for providers interested in offering quality services, and for users seeking to access relevant sources to answer their information problems. This paper outlines the efforts of the UK Joint Information Systems Committee (JISC) to help UK Higher Education Institutions deal with this growing diversity of information resources. These efforts are based on two strands: the Electronic Libraries Program and the development of the JISC Collections. These strands are now coming together as JISC concentrates on developing a Distributed National Electronic Resource (DNER), and encourages organisations to harmonise and facilitate access to this and a plethora of other resources, digital and conventional, through the model of the Hybrid Library.
Presented at the 66th IFLA Council and General Conference, 13-18 August, 2000, Jerusalem.
Keywords: digital library